Assessing the Effects of Parenting Styles on Prostitution Levels in Southern Division in Kabale Municipality. - Kemigisha, Precious (Kabale University, 2023)
Children go through different stages in life, therefore parents create their own parenting styles from a combination of factors that evolve over time as children begin to develop their personalities. During the stage of infancy, parents try to adjust to a new lifestyle in terms of adapting and bonding with their new infant. Developmental psychologists distinguish between the relationship between the child and parent, which ideally is one of attachment, and the relationship between the parent and child, referred to as bonding. In the stage of adolescence, parents encounter new challenges, such as adolescents seeking and desiring freedom. The general objective of the study was to assess the effects of parenting styles on prostitution levels in Southern Division in Kabale Municipality.